PENGARUH SUBSTITUSI TEPUNG JAGUNG VARIETAS MANADO KUNING (Zea mays L.) PADA PEMBUATAN DAGING ANALOG - Christie, Jessica; Sumual, Maria F.; Lalujan, Lana E. (Fakultas Pertanian, Universitas Sam Ratulangi, 2018)
The purpose of this study was to obtain an analogous meat formulationwith a mixture of gluten andâ€ Manado kuningâ€ corn flour based on thelevel of acceptance, and to analyze their chemical content. The statisticaldesign of this experiment was a Completely Randomized Design (CRD)with treatments of the ratio of gluten and â€œManado kuningâ€ corn flour i.e.,A (100% gluten: 0% â€œManado kuningâ€ corn flour); B (90% gluten: 10%% â€œManado kuningâ€ corn flour); C (80% gluten: 20% % â€œManadokuningâ€ corn flour); D (70% gluten: 30% % â€œManado kuningâ€ corn flour).Each treatment was repeated 3 times. The results showed that analoguemeat preferred by panelists based on color, aroam, taste, and texture wasD treatment (70% gluten: 30% % â€œManado kuningâ€ corn flour) with anaverage value of 4.75 (rather like). The chemical composition of thatanalogue meat was 61.31% water, 12.17% protein, 0.43% fat, 1.01% ash,and 24.54% carbohydrates.Keywords: Analogous Meat, Gluten, â€œManado kuningâ€ Corn Flour